New Mexico historical encyclopedia - Bullis, Don. (Los Ranchos, New Mexico Rio Grande Books, 2017)
"New Mexico Historical Encyclopedia is an encyclopedia of the history of New Mexico--the 47th State in the Union. It is a cross-section of history and people who have had an influence on life--and sometimes death--in the Land of Enchantment, from the time before the first Europeans arrived around 1540 until today. There are entries for over 500 important people and events in New Mexico's history. Possibly the most important book on New Mexico history since Ralph Emerson Twitchell -- 100 years ago"--Provided by publisher.
Includes bibliographical references (pages 859-886) and index.
108248
Keywords: New Mexico -- Biography -- Encyclopedias; Encyclopedias; History